Method for preparing environment-friendly coating from modified polyaspartic acid ester resin and isocyanate and application of environment-friendly coating

By combining modified polyasparticle resin with isocyanate, and adding long-chain olefin modified dicyclopentadiene resin and modified mixed filler, the problem of poor adhesion of polyasparticle coatings in marine environments is solved, achieving higher salt spray resistance, chemical media resistance and bending resistance, reducing maintenance costs and complexity.

CN119570342AActive Publication Date: 2025-03-07FO-SHAN CITY SANSHUI LIANMEI CHEM LTD CO

Patent Information

Application Number
CN202411120514.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-03-07
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The existing polyaspartic acid coatings have poor adhesion to PET plastic substrates in offshore environments, and are costly and complex in frequent maintenance operations.

Method used

By combining the modified polyaspartic acid resin with isocyanate, long-chain olefin modified dicyclopentadiene resin and modified mixed filler, a more complex crosslinking network is formed to improve the adhesion and chemical media resistance of the coating.

Benefits of technology

It significantly improves the adhesion of the coating on the surface of PET plastics, and enhances its salt spray resistance, chemical media resistance and bending resistance, reducing maintenance costs and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a method for preparing an environment-friendly coating from modified polyaspartic acid ester resin and isocyanate and application of the environment-friendly coating, and belongs to the technical field of coatings. The environment-friendly coating comprises the following raw materials in parts by mass: a component A: 22-27 parts of modified polyaspartic acid ester resin, 6-11 parts of polyaspartic acid ester resin, 13-18 parts of long-chain olefin modified dicyclopentadiene resin, 2-5 parts of zinc phosphate, 1-3 parts of a dispersing agent, 2-5 parts of an adhesion promoter and 12-18 parts of modified mixed filler; the component B comprises the following components in parts by weight: 75-80 parts of toluene diisocynate, 20-30 parts of HDI tripolymer, 3-5 parts of a defoaming agent and 2-3 parts of a flatting agent. The prepared environment-friendly coating is excellent in corrosion resistance, wear resistance and bending resistance, and has good adhesive force on the surface of PE T plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a method for preparing an environmentally friendly coating by using modified polyaspartic acid ester resin and isocyanate and application thereof. Background Art

[0002] In recent years, polyaspartic acid ester coatings, as a new type of high-performance coating based on aliphatic system with moderate reaction rate and excellent weather resistance, have emerged in the field of polyurea technology and are known as the "third generation of polyurea". The emergence of this type of coating indicates that while pursuing high performance, the coating industry is moving towards a greener and healthier direction.

[0003] At present, polyaspartic acid ester coatings are mostly positioned as topcoats, used in conjunction with special anticorrosive primers to form a composite coating system. Although this double-layer protection can provide excellent anticorrosion effects, it requires at least two construction processes, which not only increases the overall construction cost, but also increases the uncertainty and complexity of the construction process. Especially for those facilities operating in coastal or offshore environments, frequent maintenance operations are obviously impractical and economically burdensome.

[0004] PET plastic is used as packaging material for goods in maritime transportation, such as protective films and containers. In order to prevent seawater and moisture penetration, the outer surface of these packaging materials needs to be coated with a layer of coating. In the marine environment, due to salt spray, high humidity, strong sunlight and extreme temperature changes, PET plastic substrates are susceptible to corrosion, degradation and aging. However, the existing polyaspartic acid ester coatings do not have ideal adhesion to PET plastic substrates.

[0005] Therefore, there is an urgent need for an environmentally friendly coating that is suitable for offshore environments and has high adhesion to PET plastic equipment. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate and its application.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: The method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate comprises the following steps: (1) Weigh the following raw materials by mass: Component A: 22-27 parts of modified polyaspartic acid ester resin, 6-11 parts of polyaspartic acid ester resin, 13-18 parts of long-chain olefin modified dicyclopentadiene resin, 2-5 parts of zinc phosphate, 1-3 parts of dispersant, 2-5 parts of adhesion promoter, 12-18 parts of modified mixed filler; Component B: 75-80 parts of toluene diisocyanate, 20-30 parts of HDI trimer, 3-5 parts of defoamer, 2-3 parts of leveling agent; (2) Mixing the modified polyaspartic acid ester resin, the long-chain olefin-modified dicyclopentadiene resin, the polyaspartic acid ester resin, zinc phosphate, the modified mixed filler, the dispersant and the adhesion promoter, heating to 45-50° C., rotating at 3000-4000 rpm, and stirring for 20-30 minutes to obtain component A; (3) Mix toluene diisocyanate, HDI trimer, defoamer and leveling agent, stir at a speed of 2000-2500 rpm for 10-20 minutes to obtain component B.

[0008] Furthermore, the NH equivalent of the polyaspartic acid ester resin is 1140 g / mol and is purchased from Zhuhai Feiyang Chemical Co., Ltd., and the model is aspartic acid polyurea resin D2925.

[0009] Further, HDI trimer, Wuhan Huaxiang Kejie Biotechnology Co., Ltd., hexamethylene diisocyanate-based polyisocyanate, model HT-100.

[0010] Furthermore, the preparation method of the long-chain olefin-modified dicyclopentadiene resin comprises the following steps: S1: Add dicyclopentadiene, 1-dodecene and toluene into a stainless steel hot polymerization kettle, replace the air in the reactor with nitrogen, pressurize to 0.5-0.8MPa, and react at 180-185°C for 6-8h; after cooling to room temperature, remove unreacted olefins and toluene by vacuum distillation to obtain a long-chain olefin-modified dicyclopentadiene hot polymerization resin; S2: Add long-chain olefin-modified dicyclopentadiene thermal polymer resin, toluene and nickel-loaded catalyst in a mass ratio of 100: (120-140): 1 into a stainless steel reactor, use hydrogen to replace the air multiple times, heat to 160-165°C, introduce hydrogen to make up the pressure to 1.3-1.5MPa, hydrogenate for 4-5h, cool and release the pressure, remove toluene by reduced pressure distillation, and obtain long-chain olefin-modified dicyclopentadiene resin.

[0011] Furthermore, the mass ratio of dicyclopentadiene:1-dodecene:toluene is (7-9):(1-3):10.

[0012] Dicyclopentadiene with a purity of 90% was purchased from Shandong Maojun Chemical Industry.

[0013] The nickel-supported catalyst was purchased from Shanghai Xunkai New Material Technology Co., Ltd., model number SNCAT-8800P.

[0014] Furthermore, the preparation method of the modified polyaspartic acid ester resin is: (1) 12 parts by mass of silica sol and 2.8-3.3 parts by mass of N-[3-(trimethoxysilyl)propyl]ethylenediamine were mixed, and the mixture was stirred and reacted at 64-68°C for 26-30 hours. 1.3-1.5 parts by mass of methyl methacrylate was added, and the mixture was stirred and reacted at 72-76°C for 26-30 hours. 1-1.2 parts by mass of ethylenediamine was added, and the mixture was stirred and reacted at 25-30°C for 26-30 hours to obtain amino-functionalized silica sol. (2) Mixing amino-functionalized silica sol and hexamethylene diisocyanate, reacting at 80-85°C for 2-3h, cooling to 15-20°C, and adding hexamethylene diamine dropwise for end-capping to obtain amino-functionalized silica sol branched modified hexamethylene diamine reaction solution; (3) Add diethyl maleate dropwise to the amino-functionalized silica sol branched modified hexamethylenediamine reaction solution. After the addition is complete, the temperature is raised to 102-105° C. and the reaction is carried out at a constant temperature for 15-20 hours. Then, the unreacted raw materials are removed by vacuum rotary evaporation to obtain a modified polyaspartic acid ester resin.

[0015] The mass fraction of silicon dioxide in silica sol is 25-35%. Linyi Kehan ​​Silicon Products Co., Ltd., model: KHZCM-30.

[0016] N-[3-(Trimethoxysilyl)propyl]ethylenediamine, CAS: 1760-24-3.

[0017] Furthermore, the mass ratio of silica sol to hexamethylene diisocyanate is (0.75-0.82):1.

[0018] The molar ratio of hexamethylenediamine and hexamethylene diisocyanate is (1.2-1.5):1.

[0019] The molar ratio of diethyl maleate to hexamethylenediamine is 1:(2.5-2.8).

[0020] At present, the coating prepared by polyaspartic acid resin is mostly used as a topcoat and is used in conjunction with a special anticorrosive primer. When used alone, the coating prepared by polyaspartic acid resin has poor anticorrosive performance. The present invention can improve the salt spray resistance of the coating by compounding polyaspartic acid resin with modified polyaspartic acid resin. Modified polyaspartic acid resin and polyaspartic acid resin form a more complex cross-linked network, which can provide better permeability resistance and improve the anticorrosive performance of the coating. However, after the polyaspartic acid resin is compounded with the modified polyaspartic acid resin, the chemical medium resistance of the coating is not ideal.

[0021] The present invention further adds long-chain olefin modified dicyclopentadiene resin, which can improve the chemical medium resistance of the coating. The long-chain olefin modified dicyclopentadiene resin has good compatibility with modified polyaspartic acid ester resin and polyaspartic acid ester resin, and the long-chain olefin modified dicyclopentadiene resin itself has good chemical stability and has strong resistance to acid-base medium. The long-chain olefin modified dicyclopentadiene resin, polyaspartic acid ester resin and modified polyaspartic acid ester resin form a more dense three-dimensional network structure in the coating system, improve the high cross-linking density, and can effectively improve the compactness and stability of the coating, and then enhance its acid and alkali resistance. At the same time, the adhesion of the coating on the PET plastic surface is improved.

[0022] Furthermore, the preparation method of the modified mixed filler is: (1) Mixing nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide to obtain a mixed filler; (2) Mixing a mixed filler in a mass ratio of 1: (0.1-0.2): (8-10), a silane coupling agent KH560 and an ethanol aqueous solution with a mass fraction of 60-70%, reacting at 50-55° C. for 4-6 hours, filtering, and washing to obtain a silane-modified mixed filler; (3) A silane-modified mixed filler and N,N-dimethylformamide, N-(4-anilinophenyl)maleimide and triethylamine in a mass ratio of (2-4):(10-14):80:(0.4-0.7) are heated to 55-60°C for reaction for 20-24 hours, filtered, washed and dried to obtain a modified mixed filler.

[0023] Furthermore, the mass ratio of nano-silicon dioxide, nano-lanthanum oxide and nano-aluminum oxide is 1: (1.3-1.6): (0.5-0.8).

[0024] Furthermore, the nano-silicon dioxide has an average particle size of 20 nm and a specific surface area of ​​180 ± 50 m 2 / g.

[0025] Furthermore, the particle size of nano-lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0026] Furthermore, the average particle size of nano-alumina is 0.3 μm, and the specific surface area is 5-10 m 2 / g.

[0027] The bending resistance of the coating after long-chain olefin modified dicyclopentadiene resin is compounded with polyaspartic acid resin and modified polyaspartic acid resin is not good. Although the high cross-linking density may improve the hardness and chemical resistance of the coating, it will also reduce its flexibility. The addition of long-chain olefin modified dicyclopentadiene resin leads to a reduction in the degree of freedom between molecules, thereby making the coating more brittle and reducing the bending resistance. The present invention can improve the bending resistance of the coating by adding modified mixed fillers in the coating. The modified mixed filler can disperse stress concentration points. When the coating is subjected to bending force, the matrix material around the filler particles can disperse stress, reduce the crack formation caused by excessive local stress, and after the filler is modified, microcracks or gaps can be formed in the matrix to form "crack bridging", which can effectively delay the expansion of cracks. The surface treatment of the modified mixed filler can often improve its compatibility with the resin matrix, reduce interfacial stress, and ensure that there is good bonding between the filler and the matrix. Good interfacial bonding can prevent the filler from separating from the matrix when bending, thereby maintaining the integrity of the coating. When nano-silicon dioxide, nano-lanthanum oxide, and nano-aluminum oxide have a specific particle size and specific surface area, the wear resistance of the coating can be improved.

[0028] N-(4-anilinophenyl)maleimide, CAS number: 32099-65-3.

[0029] Furthermore, the adhesion promoter is German Walker VOK®_SILQUESTVOKA-2120 aminosilane.

[0030] The present invention provides an application of a method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate, wherein the volume ratio of the A and B components is 1:1, and the coating is used for corrosion protection of plastic material structures in the offshore petrochemical field.

[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can improve the salt spray resistance of the coating by compounding the polyaspartic acid ester resin with the modified polyaspartic acid ester resin.

[0032] 2. The present invention further adds long-chain olefin-modified dicyclopentadiene resin to improve the chemical resistance of the coating.

[0033] 3. The present invention can improve the bending resistance of the coating by adding a modified mixed filler into the coating.

[0034] 4. When nano-silica, nano-lanthanum oxide, and nano-alumina have a specific particle size and specific surface area, the wear resistance of the coating can be improved. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Some of the raw materials in the present invention are: The leveling agent is Digao TWIN-4100 leveling agent.

[0037] The defoaming agent is TEGO901W defoaming agent.

[0038] Example 1 This embodiment provides a method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate, comprising the following steps: (1) Weigh the following raw materials by mass: Component A: 24 parts of modified polyaspartic acid ester resin, 9 parts of polyaspartic acid ester resin, 15 parts of long-chain olefin modified dicyclopentadiene resin, 3 parts of zinc phosphate, 2 parts of dispersant, 4 parts of adhesion promoter, 16 parts of modified mixed filler; Component B: 77 parts of toluene diisocyanate, 25 parts of HDI trimer, 4 parts of defoamer, 2 parts of leveling agent; (2) Mixing the modified polyaspartic acid ester resin, the long-chain olefin-modified dicyclopentadiene resin, the polyaspartic acid ester resin, zinc phosphate, the modified mixed filler, the dispersant and the adhesion promoter, heating to 47° C., rotating at 3500 rpm, and stirring for 25 minutes to obtain component A; (3) Mix toluene diisocyanate, HDI trimer, defoamer and leveling agent, stir at a speed of 2200 rpm for 15 minutes to obtain component B.

[0039] The NH equivalent of the polyaspartic acid ester resin is 1140 g / mol. It was purchased from Zhuhai Feiyang Chemical Co., Ltd. and its model is aspartic acid polyurea resin D2925.

[0040] HDI trimer, Wuhan Huaxiang Kejie Biotechnology Co., Ltd., hexamethylene diisocyanate-based polyisocyanate, model HT-100.

[0041] The preparation method of long-chain olefin-modified dicyclopentadiene resin comprises the following steps: S1: Add dicyclopentadiene, 1-dodecene and toluene into a stainless steel hot polymerization kettle, replace the air in the reactor with nitrogen, pressurize to 0.6 MPa, and react at 182°C for 7 hours; after cooling to room temperature, remove unreacted olefins and toluene by vacuum distillation to obtain a long-chain olefin-modified dicyclopentadiene hot polymerization resin; S2: Add long-chain olefin-modified dicyclopentadiene thermal polymer resin, toluene and nickel-loaded catalyst in a mass ratio of 100:130:1 into a stainless steel reactor, use hydrogen to replace the air multiple times, heat to 162°C, introduce hydrogen to make the pressure up to 1.4 MPa, hydrogenate for 4.5 hours, cool and release the pressure, remove toluene by reduced pressure distillation, and obtain long-chain olefin-modified dicyclopentadiene resin.

[0042] The mass ratio of dicyclopentadiene:1-dodecene:toluene is 8:3:10.

[0043] Dicyclopentadiene with a purity of 90% was purchased from Shandong Maojun Chemical Industry.

[0044] The nickel-supported catalyst was purchased from Shanghai Xunkai New Material Technology Co., Ltd., model number SNCAT-8800P.

[0045] The preparation method of modified polyaspartic acid ester resin is: (1) 12 parts by mass of silica sol and 3 parts by mass of N-[3-(trimethoxysilyl)propyl]ethylenediamine were mixed, stirred and reacted at 65°C for 28 hours, 1.4 parts by mass of methyl methacrylate were added, stirred and reacted at 74°C for 28 hours, 1.1 parts by mass of ethylenediamine were added, stirred and reacted at 27°C for 28 hours, and amino-functionalized silica sol was obtained; (2) Mixing amino-functionalized silica sol and hexamethylene diisocyanate, reacting at 82°C for 2.5 hours, cooling to 17°C, and adding hexamethylene diamine dropwise for end-capping to obtain amino-functionalized silica sol branched modified hexamethylene diamine reaction solution; (3) Add diethyl maleate dropwise to the reaction solution of amino-functionalized silica sol branched modified hexamethylenediamine. After the addition is complete, the temperature is raised to 104°C for constant temperature reaction for 17 hours, and then the unreacted raw materials are removed by reduced pressure rotary evaporation to obtain a modified polyaspartic acid ester resin.

[0046] The mass fraction of silicon dioxide in silica sol is 25-35%. Linyi Kehan ​​Silicon Products Co., Ltd., model: KHZCM-30.

[0047] N-[3-(Trimethoxysilyl)propyl]ethylenediamine, CAS: 1760-24-3.

[0048] The mass ratio of silica sol to hexamethylene diisocyanate is 0.8:1.

[0049] The molar ratio of hexamethylenediamine to hexamethylene diisocyanate is 1.4:1.

[0050] The molar ratio of diethyl maleate to hexamethylenediamine is 1:2.7.

[0051] The preparation method of the modified mixed filler is: (1) Mixing nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide to obtain a mixed filler; (2) Mixing a mixed filler, a silane coupling agent KH560 and an ethanol aqueous solution with a mass ratio of 1:0.15:9, reacting at 52°C for 5 hours, filtering, and washing to obtain a silane-modified mixed filler; (3) A silane-modified mixed filler and N,N-dimethylformamide, N-(4-anilinophenyl)maleimide and triethylamine in a mass ratio of 3:12:80:0.5 were heated to 57°C for reaction for 22 hours, filtered, washed and dried to obtain a modified mixed filler.

[0052] The mass ratio of nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide is 1:1.5:0.7.

[0053] The average particle size of nano-silicon dioxide is 20nm, and the specific surface area is 180±50m 2 / g.

[0054] The particle size of nano-lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0055] The average particle size of nano-alumina is 0.3 μm, and the specific surface area is 5-10 m 2 / g.

[0056] N-(4-anilinophenyl)maleimide, CAS number: 32099-65-3.

[0057] The adhesion promoter is German Walker VOK®_SILQUESTVOKA-2120 aminosilane.

[0058] Example 2 This embodiment provides a method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate, comprising the following steps: (1) Weigh the following raw materials by mass: Component A: 22 parts of modified polyaspartic acid ester resin, 11 parts of polyaspartic acid ester resin, 13 parts of long-chain olefin modified dicyclopentadiene resin, 5 parts of zinc phosphate, 1 part of dispersant, 5 parts of adhesion promoter, 12 parts of modified mixed filler; Component B: 80 parts of toluene diisocyanate, 20 parts of HDI trimer, 5 parts of defoamer, 2 parts of leveling agent; (2) Mixing the modified polyaspartic acid ester resin, the long-chain olefin-modified dicyclopentadiene resin, the polyaspartic acid ester resin, zinc phosphate, the modified mixed filler, the dispersant and the adhesion promoter, heating to 50° C., rotating at 4000 rpm, and stirring for 20 minutes to obtain component A; (3) Toluene diisocyanate, HDI trimer, defoamer and leveling agent were mixed and stirred at a speed of 2500 rpm for 10 minutes to obtain component B.

[0059] The NH equivalent of the polyaspartic acid ester resin is 1140 g / mol. It was purchased from Zhuhai Feiyang Chemical Co., Ltd. and its model is aspartic acid polyurea resin D2925.

[0060] HDI trimer, Wuhan Huaxiang Kejie Biotechnology Co., Ltd., hexamethylene diisocyanate-based polyisocyanate, model HT-100.

[0061] The preparation method of long-chain olefin-modified dicyclopentadiene resin comprises the following steps: S1: Add dicyclopentadiene, 1-dodecene and toluene into a stainless steel hot polymerization kettle, replace the air in the reactor with nitrogen, pressurize to 0.8 MPa, and react at 180°C for 8 hours; after cooling to room temperature, remove unreacted olefins and toluene by vacuum distillation to obtain a long-chain olefin-modified dicyclopentadiene hot polymerization resin; S2: Add long-chain olefin-modified dicyclopentadiene thermal polymer resin, toluene and nickel-loaded catalyst in a mass ratio of 100:120:1 into a stainless steel reactor, use hydrogen to replace the air multiple times, heat to 165°C, introduce hydrogen to make up the pressure to 1.3 MPa, hydrogenate for 5 hours, cool and release the pressure, remove toluene by reduced pressure distillation, and obtain long-chain olefin-modified dicyclopentadiene resin.

[0062] The mass ratio of dicyclopentadiene:1-dodecene:toluene is 7:3:10.

[0063] Dicyclopentadiene with a purity of 90% was purchased from Shandong Maojun Chemical Industry.

[0064] The nickel-supported catalyst was purchased from Shanghai Xunkai New Material Technology Co., Ltd., model number SNCAT-8800P.

[0065] The preparation method of modified polyaspartic acid ester resin is: (1) 12 parts by mass of silica sol and 2.8 parts by mass of N-[3-(trimethoxysilyl)propyl]ethylenediamine were mixed, stirred and reacted at 68°C for 26 hours, 1.5 parts by mass of methyl methacrylate were added, stirred and reacted at 72°C for 30 hours, 1 part by mass of ethylenediamine was added, stirred and reacted at 30°C for 26 hours, and amino-functionalized silica sol was obtained; (2) mixing amino-functionalized silica sol and hexamethylene diisocyanate, reacting at 85°C for 3 h, cooling to 15°C, and adding hexamethylene diamine dropwise for end-capping to obtain amino-functionalized silica sol branched modified hexamethylene diamine reaction solution; (3) Add diethyl maleate dropwise to the reaction solution of amino-functionalized silica sol branched modified hexamethylenediamine. After the addition is complete, the temperature is raised to 105°C for constant temperature reaction for 15 hours, and then the unreacted raw materials are removed by reduced pressure rotary evaporation to obtain a modified polyaspartic acid ester resin.

[0066] The mass fraction of silicon dioxide in silica sol is 25-35%. Linyi Kehan ​​Silicon Products Co., Ltd., model: KHZCM-30.

[0067] N-[3-(Trimethoxysilyl)propyl]ethylenediamine, CAS: 1760-24-3.

[0068] The mass ratio of silica sol to hexamethylene diisocyanate is 0.82:1.

[0069] The molar ratio of hexamethylenediamine to hexamethylene diisocyanate is 1.2:1.

[0070] The molar ratio of diethyl maleate to hexamethylenediamine is 1:2.8.

[0071] The preparation method of the modified mixed filler is: (1) Mixing nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide to obtain a mixed filler; (2) Mixing a mixed filler, a silane coupling agent KH560 and a 60% ethanol aqueous solution in a mass ratio of 1:0.1:10, reacting at 55°C for 4 hours, filtering, and washing to obtain a silane-modified mixed filler; (3) A silane-modified mixed filler and N,N-dimethylformamide, N-(4-anilinophenyl)maleimide and triethylamine in a mass ratio of 4:10:80:0.7 were heated to 60°C for reaction for 20 hours, filtered, washed and dried to obtain a modified mixed filler.

[0072] The mass ratio of nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide is 1:1.6:0.8.

[0073] The average particle size of nano-silicon dioxide is 20nm, and the specific surface area is 180±50m 2 / g.

[0074] The particle size of nano-lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0075] The average particle size of nano-alumina is 0.3 μm, and the specific surface area is 5-10 m 2 / g.

[0076] N-(4-anilinophenyl)maleimide, CAS number: 32099-65-3.

[0077] The adhesion promoter is German Walker VOK®_SILQUESTVOKA-2120 aminosilane.

[0078] Comparative Example 1 The difference between this comparative example and Example 1 is that 24 parts of modified polyaspartic acid ester resin, 9 parts of polyaspartic acid ester resin, and 15 parts of long-chain olefin-modified dicyclopentadiene resin are replaced by: 19 parts of modified polyaspartic acid ester resin, 2 parts of polyaspartic acid ester resin, and 9 parts of long-chain olefin-modified dicyclopentadiene resin.

[0079] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation method of the modified polyaspartic acid ester resin is: (1) In a nitrogen-protected reactor, add a 20% trichlorosilane ethanol solution, add deionized water dropwise under stirring, the molar ratio of deionized water to trichlorosilane is 1:3, react at a temperature of 75°C for 0.5 hour, then add hexamethylene diisocyanate, and continue to react for 0.5 hour to obtain a pre-reaction liquid; the mass ratio of trichlorosilane to hexamethylene diisocyanate is 0.8:1; (2) controlling the temperature of the reaction kettle to be within the range of 15° C. by water cooling, adding hexamethylenediamine end-capping agent dropwise to the above-mentioned pre-reaction liquid under stirring to obtain a silicon-block branched modified organic diamine reaction liquid; the molar ratio of hexamethylenediamine to hexamethylene diisocyanate is 1.4:1; (3) Slowly add dimethyl maleate to the above silicon block branched modified organic diamine reaction solution using a titration funnel. The molar ratio of diethyl maleate to hexamethylenediamine is 1:2.7. After the addition is complete, the temperature is raised to 90°C and the reaction is carried out at a constant temperature for 10 hours. Then, the solvent is removed to obtain a modified polyaspartic acid ester resin.

[0080] Comparative Example 3 The difference between this comparative example and Example 1 is that the mass ratio of nano-silicon dioxide, nano-lanthanum oxide and nano-aluminum oxide is 1:1:1.

[0081] Comparative Example 4 The difference between this comparative example and Example 1 is that the average particle size of the nano-silicon dioxide is 80 nm, and the specific surface area is 60 ± 20 m 2 / g. The particle size of nano-lanthanum oxide is 1μm-5μm, and the specific surface area is 1-10m 2 / g. The average particle size of nano-alumina is 10μm, and the specific surface area is 1-5m 2 / g.

[0082] Comparative Example 5 The difference between this comparative example and Example 1 is that 24 parts of modified polyaspartic acid ester resin, 9 parts of polyaspartic acid ester resin and 15 parts of long-chain olefin-modified dicyclopentadiene resin are replaced by 24 parts of modified polyaspartic acid ester resin and 24 parts of polyaspartic acid ester resin.

[0083] Comparative Example 6 The difference between this comparative example and Example 1 is that the NH equivalent of the polyaspartic acid ester resin is 230 g / mol and it was purchased from Zhuhai Feiyang Chemical Co., Ltd. and its model is aspartic acid polyurea resin F220.

[0084] Comparative Example 7 The difference between this comparative example and Example 1 is that the mass ratio of dicyclopentadiene:1-dodecene:toluene is 5:4:10.

[0085] Performance Testing 1. Refer to GB / T5210-2006 to measure the adhesion of coating on PET plastic surface; 2. According to GB / T1771-2007, the salt spray resistance of the coating is measured for 4200h. If there is no blistering, rusting, cracking or falling off, it is considered as compliance, otherwise it is considered as non-compliance; 3. Refer to GB / T9274-1988 to test the chemical resistance of the coating (room temperature for 720h), 10wt% sodium hydroxide, 10wt% sulfuric acid. If there is no peeling, wrinkling, cracking, blistering or rusting, it is considered as compliance. Otherwise, it is considered as non-compliance. 4. Determine the abrasion resistance of the coating (1000g / 1000r.CS-10) according to GB / T1768-2006; 5. Refer to Appendix D of SY / T0315 to measure the bending resistance of the coating (-20℃, 1.5°).

[0086] 6. Refer to GB / T1766-2008 to measure the UV aging resistance of the coating (UVB-313Lamp. 1440h). If there is no blistering, rusting, cracking or peeling, and the color change is level 0, the gloss loss is level 1 and the powdering is level 0, it is recorded as compliance, otherwise it is recorded as non-compliance.

[0087] Table 1 Performance test results

[0088] It can be seen from the above performance test results that the comprehensive performance of Examples 1-2 is excellent, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly because the synergistic effect of multiple components improves the comprehensive performance of the coating.

[0089] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratio of modified polyaspartic acid resin, polyaspartic acid resin, and long-chain olefin modified dicyclopentadiene resin is changed, and it can be seen that the corrosion resistance effect decreases, proving that the three resin compounding schemes have an important influence on the corrosion resistance effect of the coating. The preparation method of the modified polyaspartic acid resin in comparative example 2 is different, and the salt spray resistance performance decreases, indicating that only the polyaspartic acid resin prepared by the present invention and the modified polyaspartic acid resin are compounded to improve the salt spray resistance of the coating. The preparation conditions of the modified mixed fillers in comparative examples 3-4 are different, and it can be seen from the results that the bending resistance and wear resistance of the coating are affected. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect. In Comparative Example 5, the ratio of modified polyaspartic acid ester resin, polyaspartic acid ester resin, and long-chain olefin modified dicyclopentadiene resin was changed, and the adhesion, chemical resistance, and salt spray resistance of the coating decreased, indicating that the ratio of the three had an important influence on the performance of the coating. Comparative Example 6 used polyaspartic acid ester resins with different NH equivalents, and Comparative Example 7 prepared long-chain olefin modified dicyclopentadiene resins with different mass ratios of dicyclopentadiene: 1-dodecene: toluene, all of which had an impact on the performance of the coating.

[0090] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and an isocyanate, characterized in that: The following steps are involved: (1) Weigh the following raw materials by mass: Component A: 22-27 parts of modified polyaspartic acid ester resin, 6-11 parts of polyaspartic acid ester resin, 13-18 parts of long-chain olefin modified dicyclopentadiene resin, 2-5 parts of zinc phosphate, 1-3 parts of dispersant, 2-5 parts of adhesion promoter, 12-18 parts of modified mixed filler; The preparation method of long-chain olefin-modified dicyclopentadiene resin comprises the following steps: S1: Add dicyclopentadiene, 1-dodecene and toluene into a stainless steel hot polymerization kettle, replace the air in the reactor with nitrogen, pressurize to 0.5-0.8MPa, and react at 180-185°C for 6-8h; after cooling to room temperature, remove unreacted olefins and toluene by vacuum distillation to obtain a long-chain olefin-modified dicyclopentadiene hot polymerization resin; S2: Add a long-chain olefin-modified dicyclopentadiene thermal polymer resin, toluene and a nickel-supported catalyst in a mass ratio of 100: (120-140): 1 into a stainless steel reactor, use hydrogen to replace the air multiple times, heat to 160-165° C., introduce hydrogen to make up the pressure to 1.3-1.5 MPa, hydrogenate for 4-5 hours, cool and release the pressure, remove toluene by vacuum distillation, and obtain a long-chain olefin-modified dicyclopentadiene resin; Component B: 75-80 parts of toluene diisocyanate, 20-30 parts of HDI trimer, 3-5 parts of defoamer, 2-3 parts of leveling agent; (2) Mixing the modified polyaspartic acid ester resin, the long-chain olefin-modified dicyclopentadiene resin, the polyaspartic acid ester resin, zinc phosphate, the modified mixed filler, the dispersant and the adhesion promoter, heating to 45-50° C., rotating at 3000-4000 rpm, and stirring for 20-30 minutes to obtain component A; (3) Mix toluene diisocyanate, HDI trimer, defoamer and leveling agent, stir at a speed of 2000-2500 rpm for 10-20 minutes to obtain component B.

2. The method for preparing an environmentally friendly coating from a modified polyaspartic acid ester resin and isocyanate according to claim 1, characterized in that: The NH equivalent weight of the polyaspartic acid ester resin is 1140 g / mol.

3. The method for preparing an environmentally friendly coating from a modified polyaspartic acid ester resin and isocyanate according to claim 1, characterized in that: The mass ratio of dicyclopentadiene:1-dodecene:toluene is (7-9):(1-3):

10.

4. The method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate according to claim 1, characterized in that: The preparation method of modified polyaspartic acid ester resin is: (1) 12 parts by mass of silica sol and 2.8-3.3 parts by mass of N-[3-(trimethoxysilyl)propyl]ethylenediamine were mixed, and the mixture was stirred and reacted at 64-68°C for 26-30 hours. 1.3-1.5 parts by mass of methyl methacrylate was added, and the mixture was stirred and reacted at 72-76°C for 26-30 hours. 1-1.2 parts by mass of ethylenediamine was added, and the mixture was stirred and reacted at 25-30°C for 26-30 hours to obtain amino-functionalized silica sol. (2) Mixing amino-functionalized silica sol and hexamethylene diisocyanate, reacting at 80-85°C for 2-3h, cooling to 15-20°C, and adding hexamethylene diamine dropwise for end-capping to obtain amino-functionalized silica sol branched modified hexamethylene diamine reaction solution; (3) Add diethyl maleate dropwise to the amino-functionalized silica sol branched modified hexamethylenediamine reaction solution. After the addition is complete, the temperature is raised to 102-105° C. and the reaction is carried out at a constant temperature for 15-20 hours. Then, the unreacted raw materials are removed by vacuum rotary evaporation to obtain a modified polyaspartic acid ester resin.

5. The method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate according to claim 1, characterized in that: The preparation method of the modified mixed filler is: (1) Mixing nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide to obtain a mixed filler; (2) Mixing a mixed filler in a mass ratio of 1: (0.1-0.2): (8-10), a silane coupling agent KH560 and an ethanol aqueous solution with a mass fraction of 60-70%, reacting at 50-55° C. for 4-6 hours, filtering, and washing to obtain a silane-modified mixed filler; (3) A silane-modified mixed filler and N,N-dimethylformamide, N-(4-anilinophenyl)maleimide and triethylamine in a mass ratio of (2-4):(10-14):80:(0.4-0.7) are heated to 55-60°C for reaction for 20-24 hours, filtered, washed and dried to obtain a modified mixed filler.

6. The method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate according to claim 5, characterized in that: The mass ratio of nano silicon dioxide, nano lanthanum oxide and nano aluminum oxide is 1: (1.3-1.6): (0.5-0.8).

7. The method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate according to claim 5, characterized in that: The average particle size of nano-silicon dioxide is 20nm, and the specific surface area is 180±50m 2 / g.

8. The method for preparing an environmentally friendly coating from a modified polyaspartic acid ester resin and isocyanate according to claim 5, characterized in that: The particle size of nano-lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

9. The method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate according to claim 5, characterized in that: The average particle size of nano-alumina is 0.3 μm, and the specific surface area is 5-10 m 2 / g.

10. The use of the method for preparing an environmentally friendly coating by using a modified polyaspartic acid ester resin and isocyanate according to any one of claims 1 to 9, characterized in that: The volume ratio of the A and B components is 1:1, and the coating is used for anti-corrosion of plastic material structures in the offshore petrochemical industry.

Citation Information

Patent Citations

  • Pollution flashover preventing insulating coating with micro-nano composite particles added and preparing technology

    CN105086826A

  • Primer-topcoat type solvent-free polyaspartic acid ester heavy anti-corrosion coating and preparation method and application thereof

    CN113637398A

  • Antibacterial acrylic resin emulsion for stabilizing nano-silver and preparation process

    CN117925020A

  • Manufacturing Method Of Hard Metal

    KR102009171B1

  • KR20240037164A

Cited By

  • Preparation method and application of environment-friendly coating based on epoxy-silicon synergistic crosslinking

    CN121718258A